Comparison of oxygen reserve index according to the remimazolam or dexmedetomidine for intraoperative sedation under regional anesthesia—A single-blind randomized controlled trial - Lee, Sangho; Kim, MinSung; Kang, Hee Yong; Choi, Jeong-Hyun; Kim, Mi Kyeong; You, Ann Hee (Frontiers in Medicine, 2023)
Introduction: We aimed to evaluate the difference in intraoperative oxygen reserve index (ORi) between the sedatives remimazolam (RMMZ) and dexmedetomidine (DEX). Methods: Seventy-eight adult patients scheduled for sedation under regional anesthesia were randomly assigned to either the DEX (n=39) or RMMZ (n=39) group. The primary outcome was the difference in perioperative ORi between the groups. The secondary outcomes included respiratory depression, hypo- or hypertension, heart rate (HR), blood pressure, respiratory rate and postoperative outcomes. Additionally, the number of patients who experienced a decrease in intraoperative ORi to < 50% and the associated factors were analyzed. Results: The ORi was significantly higher in the RMMZ group at 15 min after sedation maintenance. There were no significant differences in respiratory depression between the two groups. The intraoperative HR was significantly higher in the RMMZ group after the induction of sedation, 15 min after sedation maintenance, and at the end of surgery. No other results were significantly different between the two groups. The incidence of a decrease in intraoperative ORi to < 50% was significantly higher in the DEX group. Factors associated with a decrease in the intraoperative ORi to < 50% were diabetes mellitus, low baseline peripheral oxygen saturation (SpO2), and DEX use. In the receiver operating characteristic curve analysis for a decrease in the intraoperative ORi to < 50%, the cutoff baseline SpO2 was 97%. Conclusion: RMMZ is recommended as a sedative for patients with a low baseline SpO2 and intraoperative bradycardia. Further studies should be conducted to establish the criteria for a significant ORi reduction.